ANALISIS POTENSI PENERIMAAN NEGARA BUKAN PAJAK SEKTOR PERIKANAN TANGKAP (ANALYSIS THE POTENTIAL OF NON-TAX GOVERNMENT REVENUE FROM FISHERIES SECTOR) - Agunan P. Samosir, Rita Helbra Tenrini & Anda Nugroho (Jurnal Borneo Administrator: Media Pengembangan Paradigma dan Gaya Baru Manajemen Pemerintahan Daerah, 2015)
Realization of non-tax government revenues from fisheries sector since 2006is still far from its potential and actual targets. Though the volume of production from fisheries results tend to research year and in 2012 reached 5.8 million tons and production rate of Rp.72,01trillion. Non-tax government revenues from fisheries in 2012 only amounted about 0.3 percent from the production value of fisheries in Indonesia. Some of region in Indonesia were already experiencing over fishing. If there is no action from the government to control fishing activities, then fisheries sustainability would be threatened. The purpose of this study is to analyze and estimate the potential of non-tax government revenues from fisheries sector. The research method used is a combination of quantitative method (to make analysis about the potential of non-tax government revenues from fisheries sector and its impact to fishers welfare)and qualitative method(to identify problems from every cycle in fisheries management). The results are surprising because of the potential of non-tax government revenues from fisheriesin 2014 could reach 10 times than the realizationin 2012. Keywords: non-tax government revenues, fisheries, fisheries sustainability.